Emerging giants, aspiring multinationals, and foreign executives: leapfrogging, capability building, and competing with developed country multinationals - Arp, Frithjof (Wiley, 2014)
The phenomenon of emerging‐market organizations appointing foreign executives from distant cultural contexts to headquarters positions has stirred public and academic interest. Emerging giants, aspiring multinationals, and even local organizations that focus entirely on domestic markets have joined the global hunt for management talent. This article reports why foreign executives from significant cultural distance are appointed to local headquarters positions, what they contribute, and why these positions are not filled with local executives. Data are sourced from in‐depth interviews with two sample groups in organizations founded and headquartered in Malaysia (46 foreign executives from 13 countries and 25 host‐country peers from three local ethnocultural groups). Triangulation of dyadic data from these two sample groups reveals a dichotomy between the initial reasons for which foreign executives are appointed and the continued reasons why some of these executives remain in their positions.